Grammatical Subjects in Home Sign: Abstract Linguistic Structure in Adult Primary Gesture Systems without Linguistic Input - Marie Coppola; Newport, Elissa L. (Proceedings of the National Academy of Sciences - PNAS, 2005)
Language ordinarily emerges in young children as a consequence of both linguistic experience (for example, exposure to a spoken or signed language) and innate abilities (for example, the ability to acquire certain types of language patterns). One way to discern which aspects of language acquisition are controlled by experience and which arise from innate factors is to remove or manipulate linguistic input. However, experimental manipulations that involve depriving a child of language input are impossible. The present work examines the communication systems resulting from natural situations of language deprivation and thus explores the inherent tendency of humans to build communication systems of particular kinds, without any conventional linguistic input. We examined the gesture systems that three isolated deaf Nicaraguans (ages 14-23 years) have developed for use with their hearing families. These deaf individuals have had no contact with any conventional language, spoken or signed. To communicate with their families, they have each developed a gestural communication system within the home called "home sign." Our analysis focused on whether these systems show evidence of the grammatical category of Subject. Subjects are widely considered to be universal to human languages. Using specially designed elicitation tasks, we show that home signers also demonstrate the universal characteristics of Subjects in their gesture productions, despite the fact that their communicative systems have developed without exposure to a conventional language. These findings indicate that abstract linguistic structure, particularly the grammatical category of Subject, can emerge in the gestural modality without linguistic input.